Baylisascaris as a differential diagnosis of larva migrans in humans, Costa Rica. - Baldi Salas, Mario (2018)
Baylisascariosis is a disease caused by a very aggressive migrating larva in humans and animals, which is classified as an emerging zoonosis of importance in public health. The causal agent is the nematode Baylisascaris procyonis, its definitive host is the common raccoon ( Procyon lotor). Reports of B. procyonis presence in raccoon´s populations in the urban zone of Costa Rica, it is an alert on the need to understand its life cycle, and to learn about its diagnosis, transmission and prevention. This review contemplates the most relevant aspects of the nematode in relation to public health. Public and animal health workers need to consider Baylisascaris procyonis within their differential diagnoses of migratory larvae caused by other nematodes of the order Ascaridida in Costa Rica and possibly in the Mesoamerican and nd Caribbean regions.